Pemanfaatan Media Pembelajaran IPA terhadap Hasil Belajar Siswa Kelas V di SD Negeri 091 Palembang - Samian Hakim; Lukman Hakim; Treny Hera (Journal on Education, 2023)
This study aims to determine the influence of the use of science learning media on the learning outcomes of grade V students at SD Negeri 091 Palembang. In this study, it uses the experimental research method "To experiment is to try, to look for, to confirm". The population in this study was grade V students of SD Negeri 091 Palembang with a total population of 48 students and the number of samples used was 25 students. The data collection techniques used in this study were tests and documentation. This study concluded that the work hypothesis (Ha) in this study was accepted, and there was an increase in learning outcomes of grade V students. those using image media further enhance significant learning outcomes. Proven in the t test analysis, the calculation results were obtained, namely (3.8088 > 1.679). This proves that there is a significant influence on the use of learning media on the learning outcomes of grade V students of SD Negeri 091 Palembang.